Blind Separation of Abdominal Electrocardiogram Sources through Dynamic Neural Network; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Devyatykh D. V. Dmitry Vladimirovich (2016, 2016)
Title screen